Surface sediment grain-size distribution and sediment transport in the subaqueous Mekong Delta, Vietnam - Thanh*, Nguyen Trung; Stattegger, Karl; Unverricht, Daniel; Nittrouer, Charles; Phach, Phung Van; Liu, Paul; DeMaster, David; Dung, Bui Viet; Anh, Le Duc; Dong, Mai Duc (Vietnam Journal of Earth Sciences, 2017)
The sediment transport around the Mekong delta was clarified by using geochemical data and modeling indicating the southwestward transport of re-suspended sediments under the influence of NE monsoon. However, the detail pattern of grain-size distribution of the surface sediments in the subaqueous Mekong River delta has not been well understood. This paper presents characteristics of grain-size parameters of the surface sediments in order to interpret the sediment-transport pattern and the linkage to coastal erosion and deposition off the Mekong River delta. Surface sediments collected in the coastal water of Mekong River delta (as far south as Ca Mau Peninsula) were analyzed to determine the grain-size distribution and sediment transports in subaqueous Mekong delta. Results indicated that the net sediment transport was southwestward to the Ca Mau peninsula and the sediments were finer from the delta topset downward the delta foreset. In contrast, the sediment particles on the adjacent inner shelf were coarser and are more poorly sorted due to the increase in carbonate shell fragments and the Early Holocene sediments. The sediment grain-size parameters were variable in different sedimentary sub-environments of the subaqueous Mekong delta and controlled by the distance of sediment transport, the hydrodynamic regime of each region and coastal erosion of the delta coast. References Anthony J.E., Brunier G., BessetM., Goichot M., Dusouillez P, Nguyen V.L., 2015. Linking repid erosion of the Mekong River delta to human activities. Scientific Reports, 1-12. Blott S.J and Pye K., 2001. Gradistat: a grain size distrubution and statistics package for the analysis of unconsolidated sediments, Technical Communication. Earth Surface Processes and Landforms, 26, 1237-1248. Dung B.V., Schimanski A., Stattegger K., Phach P.V., Tiep N.T., Hai N.T., Thanh N.T., Phi T.T., 2009. Sandwaves on the Southeast Vietnam Shelf recorded by high resolution seismic profiles: formation and mechanism. Front. Earth Sci. China, 3(1), 9-20. Dung B.V., Stattegger K., Unverricht, D., Phach P.V.,Thanh N.T.,2013. Late Pleistocene-Holocene seismic stratigraphy of the Southeast Vietnam Shelf. Global and Planetary Change 110, 156-169. Hein H., Hein B., Pohlmann T., 2013. Recent dynamics in the region of Mekong water influence. Global and Planetary Change, 110, 183-194. Folk R.L and Ward W.C., 1957. Brazos River bar: a study in the significance of grain size parameters. Journal of Sedimentary Petrology, 27, 3-26. Liu S., Lu P., Liu D., Jin P and Wang W., 2009. Pinpointing source and measuring the lengths of the principal rivers of the world. International Journal of Digital Earth, 2, 80-87. doi:10.1080/17538940902746082. Mothersill J., 1969. A grain size analysis of longshore bars and troughs, Lake Superior, Ontario. Journal of Sedimentary Petrology, 39, 1317-1324.Milliman J.D., and Meade R.H., 1983. World-wide delivery of river sediments to the ocean. Journal of Geology, 91, 1-21. Milliman J.D., Syvistski J.P.M., 1982. Geomorphic/tectonic control of sediment discharge to the oceans: the importance of small mountain rivers. Journal of Geology, 100, 525-544. Pettijohn F.G., Ridge J.D., 1932. A textural variation series of beach sands from Cedar Point, Ohio, Journal of Sedimentary Petrology, 2, 76-88. Ninh P.V (Ed.)., 2003. South China Sea Monograph, Vol II-Meteorology, Marine Hydrology and Hydrodynamics, Hanoi National University Publisher., 565p., Hanoi (in Vietnamese). Nowacki D.J., Ogston A.S., Nittrouer C.A., Fricke A.T, and Tri V.P.D., 2015. Sediment dynamics in the lower Mekong River: Transition from tidal river to estuary. J.Geophys,Res, Oceans, 120, 6363-6383, doi:10.1002/2015JC010754. Kubicki, A., 2008. Large and very large subaqueous delta dunes on the continental shelf off southern Vietnam, South China Sea. Geo-Mar. Lett, 28, 229-238. Doi:10.1007/s00367-008-0103-9. Sibson R., 1981. A brief description of natural neighbor interpolation, in V. Barnett, ed., Interpreting Multivariate Data: John Wiley & Sons, 21-36. Stattegger K., Tjallingii R., Saito Y., Michelli M., Thanh N.T., Wetzel A., 2013. Mid to late Holocene sea-level reconstruction of Southeast Vietnam using beachrock and beach-ridge deposits. Global and Planetary Change, 110, 214-222. Szczuciński W., Jagodziński R., Hanebuth T.J.J., Stattegger K., Wetzel A., Mitręga M., Unverricht D., Phach P.V., 2013. Modern sedimentation and sediment dispersal pattern on the continental shelf off the Mekong River delta, South China Sea. Global and Planetary Change, 110, 195-213. Ta T.K.O., Nguyen V.L., Kobayashi I., Tateishi M and Saito Y., 2001. Late Pleistocene-Holocene stratigraphy and delta progradation, the Mekong River delta, South Vietnam. Gondwana Research, 4(4), 779. Ta T.K.O., Nguyen V.L., Tateishi M., Kobayashi I., Saito Y., Nakamura T., 2002a. Sediment facies and Late Holocene progradation of the Mekong River Delta in Bentre Province, southern Vietnam: an example of evolution from a tide-dominated to a tide- and wave-dominated delta. Sedimentary Geology, 152, 313-325. Doi 10.1007/s11707-009-0002-z. Ta T.K.O, Nguyen V.L., Tateishi M., Kobayashi I., Tanabe S., Saito Y., 2002b. Holocene delta evolution and sediment discharge of the Mekong River, southern Vietnam: Quaternary Science Reviews, 21, 1807-1819. Tamura T., Saito Y., Sieng S., Ben B., Kong M., Choup S., Tsukawaki S., 2007. Depositional facies and radiocarbon ages of a drill core from the Mekong River lowland near Phnom Penh, Cambodia: evidence for tidal sedimentation at the time of Holocene maximum flooding. J. Asian Earth Sci., 29, 585-592. Tamura T., Saito Y., Sieng S., Ben B., Kong M., Sim I., Choup S., Akiba F., 2009. Initiation of the Mekong River delta at 8 ka: evidence from the sedimentary succession in the Cambodian lowland. Quaternary Science Review, 28, 327-344. Thanh N.T., Phach P.V., Dung B.V., Statteger K., Anh L D., Anh P.T., 2014. Sedimentary evolution on the inner shelf adjacent to the Camau Pennisular in the lastest Late Pleistocene-Holocene. Journal of Marine Science and Technology (in Vietnamese). Tjallingii R., Stattegger K., Wetzel A., Phach P.V., 2010. Infilling and flooding of the Mekong River incised valley during deglacial sea-level rise. Quaternary Science Reviews, 29, 1432-1444. Xue Z, Liu J.P., DeMaster D., Nguyen V.L., Ta T.K.O., 2010. Late Holocene Evolution of the Mekong Subaqueous Delta, Southern Vietnam. Marine Geology, 269, 46-60. Xue Z., Liu J.P., Ge Q., 2011. Changes in hydrology and sediment delivery of the Mekong River in the last 50 years: connection to damming, monsoon, and ENSO. Earth Surf. Process. Landforms, 36, 296-308. Xue Z., He R., Liu J.P., Warner J.C., 2012. Modeling transport and deposition of the Mekong River sediment. Continental Shelf Research, 37, 66-78. Xue Z., Liu J.P., DeMaster D., Leithold E L., Wan S., Ge Q., Nguyen V.L., Ta T.K.O., 2014. Sedimentary processes on the Mekong subaqueous delta: Clay mineral and geochemical analysis. Journal of Asian Earth Sciences,79, 520-528. Unverricht D., Szczuciński W., Statteger K., Jagodziński R., Le X.T., Kwong L.L.W., 2013. Modern sedimentation and morphology of the subaqueous Mekong Delta, Southern Vietnam. Global and Planetary Change, 110, 223-235. Wolanski E., Nguyen N.H., Spagnol S., 1998. Sediment dynamics during low flow conditions in the Mekong River Estuary, Vietnam. Journal of Coastal Research, 14, 472-482. Wolanski E., Ngoc Huan N., Trong Dao L., Huu Nhan N., Ngoc Thuy N., 1996. Fine sediment dynamics in the Mekong River Estuary, Vietnam. Estuar. Coast. Shelf Sci, 43, 565-582.